1992
DOI: 10.1111/j.1533-8525.1992.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Generation, and School Attainment of Asians, Hispanics, and Non-Hispanic Whites

Abstract: Research on immigration and attainment in U.S. schools typically does not separate out generation of U.S. residence, a critical factor in attainment. This article explores immigrant generation effects (native, child of immigrant, immigrant) on schooling attained for Asians, Hispanics, and non-Hispanic whites, using Current Population Survey data. Previously unpublished cross-sectional data are presented. Regressions predicting school years completed show variable generation-by-ethnicity effects. Asian attainme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 19 publications
6
36
0
1
Order By: Relevance
“…These factors are along the lines of previous studies in that pupils of immigrant mothers may perform worse than those of native mothers (e.g., Fernandez-Kelly and Schauffler, 1994; Jain and Belsky, 1997; Leidy et al, 2009;Van Amersfoort, 1974;Rosenthal et al, 1983;Lareau, 1989;Rong and Grant, 1992;Cosden et al, 1995;Kao and Tienda, 1995). The point is that the ineffective learning of pupils with immigrant mothers does not pertain to the pupils themselves, but can be attributed to their feeling that they are not treated in a "seems fair" environment.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…These factors are along the lines of previous studies in that pupils of immigrant mothers may perform worse than those of native mothers (e.g., Fernandez-Kelly and Schauffler, 1994; Jain and Belsky, 1997; Leidy et al, 2009;Van Amersfoort, 1974;Rosenthal et al, 1983;Lareau, 1989;Rong and Grant, 1992;Cosden et al, 1995;Kao and Tienda, 1995). The point is that the ineffective learning of pupils with immigrant mothers does not pertain to the pupils themselves, but can be attributed to their feeling that they are not treated in a "seems fair" environment.…”
Section: Resultssupporting
confidence: 73%
“…Given the fact that the children from immigrant families in Taiwan are generally less advantaged in terms of family background and social status (which will be shown in Section 4), we expect that the native-born students will tend to perform better than second-generation students in terms of academic achievement. This can be justified by previous studies that found that the disadvantageous language proficiency of the foreign spouses (mainly the pupils' mothers) contributes to the inferior performance of the second-generation students (Rosenthal et al, 1983;Rong and Grant, 1992;Cosden et al, 1995;Kao and Tienda, 1995), that the parents' disadvantaged socio-economic positions may carry over to the next generations (Van Amersfoort, 1974), and that the lack of common interest or mutual understanding between school -6 -teachers and parents may hamper the learning of the "New-Taiwanese Offspring" (Lareau, 1989). In addition, the foreign brides in Taiwan can be roughly grouped into mainland China and Southeast Asian brides based on their country of origin, where Mandarin is the common language shared by both sides of the Taiwan Strait.…”
Section: Theoretical Argumentsmentioning
confidence: 95%
“…The immigration status of the family has received special attention in recent years. Empirical evidence indicates that students born abroad tend to underperform (even after controlling for other significant variables), while there are no significant differences between national students and students born in the country to foreign parents (see Calero & Escardíbul, 2007;Chiswick & Debburman, 2004;Kao & Tienda, 1995;Rong & Grant, 1992). Schnepf (2008), using TIMSS, PIRLS and PISA data for a set of eight OECD countries, shows that in general there is great heterogeneity within the group of immigrant students, the dispersion of their educational outcomes being higher than that of national students.…”
Section: Determinants Of Educational Outcomes: Literature Reviewmentioning
confidence: 99%
“…Our results do not confirm this hypothesis for the whole sample but are highly significant for the Hispanic subsample when using both categorical and linear analyses and only just significant for the white subsample when using the linear analysis. In the NSFG, about half of Hispanic women of reproductive age (15−44 years) and living in households are foreign born (Daniels, Mosher, and Jones 2013;Jones, Mosher, and Daniels 2012), so it may be that, as a recent immigrant group, Hispanics are especially attentive to the importance of higher education and what it can mean for family welfare (Lopez 2009;Rong and Grant 2005).…”
Section: Discussionmentioning
confidence: 99%